Mutations of the SARS-CoV-2 Spike Glycoprotein Detected in Cats and Their Effect on Its Structure and Function - Hamdy, Mervat E.; El-Deeb, Ayman H.; Hagag, Naglaa M.; Shahein, Momtaz A.; Alaidi, Osama; Hussein, Hussein A. (Frontiers in Cellular and Infection Microbiology, 2022)
The high frequency of Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) mutations and homology of the Angiotensin-Converting Enzyme-2 (ACE2) cell receptors in various hosts help the virus transcend species barriers. In this study, we investigated the mutations of the SARS-CoV-2 spike glycoprotein detected in cats and their effect on its structure and function. Interestingly, some of these mutations are reported here in cats for the first time. Structural analysis showed seven residue substitutions in the spike glycoprotein. Four of the detected mutations are located on the spike surface, which are critical interaction points for neutralizing antibodies. Furthermore, three of the reported mutations could facilitate viral binding to the ACE2 host receptor, influence S1/S2 cleavage, destabilize the β-hairpin structure of the S2 and enhance viral infectivity. Structural modeling and phylogenic analysis of the ACE2 receptor provided an indication of the binding capacity of the virus to the specific cell receptors of different species and hosts. The presented work highlights the effects of the residue substitutions on viral evasion, infectivity and possibility of SARS-CoV-2 spillover between humans and cats. In addition, the work paves the way for in-depth molecular investigation into the relationship between SARS-CoV-2 receptor binding and host susceptibility.